Legal Protection of Industrial Design Information and Communication Technology Based on Creative Economy to Improve Community Competitiveness - Abdul Atsar (Universitas Airlangga, 2019)
Law is very influenced on the development of Technology. The current legal tool has no readiness so that it can not keep up with the rapid technological advances. The purpose of this study is to analyze the application of regulation on protection system and law enforcement of ICT design based on creative economy to improve people's competitiveness. Research is a normative juridical study. The approach of this research is the approach of legislation, concepts and cases. This research is analytical descriptive. This study, using secondary data sources. Technique of collecting data with literature study. Data analysis technique by qualitative normative descriptive method.The regulation of the legal protection system of industrial design of ICT, in Law no. 31 Year 2000, has not been regulated explicitly about the element of novelty, the application of constitutive stelsel cause obstacles. The law enforcement of ICT design is not yet effective, because of three aspects: 1) The legal substance aspect is not yet explicitly regulated about the novelty element in Industrial Design terms and the qualification and classification of the object of Right, the substantive requirement of Right of Industrial Design, the provisions of sanctions that distinguish between rights violations caused by the substance of the